Sea Urchin Extracellular Proteins Design a Complex Protein Corona on Titanium Dioxide Nanoparticle Surface Influencing Immune Cell Behavior - Alijagic, Andi; Benada, Oldřich; Kofroňová, Olga; Cigna, Diego; Pinsino, Annalisa (Frontiers in Immunology, 2019)
Extensive exploitation of titanium dioxide nanoparticles (TiO2NPs) augments rapid release into the marine environment. When in contact with the body fluids of marine invertebrates, TiO2NPs undergo a transformation and adhere various organic molecules that shape a complex protein corona prior to contacting cells and tissues. To elucidate the potential extracellular signals that may be involved in the particle recognition by immune cells of the sea urchin Paracentrotus lividus, we investigated the behaviour of TiO2NPs in contact with extracellular proteins in vitro. Our findings indicate that TiO2NPs are able to interact with sea urchin proteins in both cell-free and cell-conditioned media. The two-dimensional proteome analysis of the protein corona bound to TiO2NP revealed that negatively charged proteins bound preferentially to the particles. The main constituents shaping the sea urchin cell-conditioned TiO2NP protein corona were proteins involved in cellular adhesion (Pl-toposome, Pl-galectin-8, Pl-nectin) and cytoskeletal organization (actin and tubulin). Immune cells (phagocytes) aggregated TiO2NPs on the outer cell surface and within well-organized vesicles without eliciting harmful eﬀects on the biological activities of the cells. Cells showed an active metabolism, no oxidative stress or caspase activation. These results provide a new level of understanding of the extracellular proteins involved in the immune-TiO2NP recognition and interaction in vitro, confirming that primary immune cell cultures from P. lividus can be an optional model for swift and efficient immune-toxicological investigations.